Colombia: la recuperación de un destino turístico en coma (2019)
Colombia is considered us one of the most violent countries in Latinoamerica in the last 50 years, this situation has affected it’s image as a tourist destination, influencing the tourist’s perception, destination selection, tourist security and evidently the international tourist arrivals in the country. However, Colombia started using Tourism promotion as a marketing tool, to make known the world those positives and unknown aspects that could change the world’s perception of the country. In the present research, is built a timeline to identify every promotional campaign as Tourism promotion strategies implemented by the nation in each presidencial period in the last century and how these influenced and impacted the tourist development of a country that was under a bad perception that didn’t allow it to potentiate the tourist activity. This work managed to identify each promotional campaign, divided into 3 timelines: National Tourism Promotion, International Tourism Promotion and Country-Brand, because each one has a different focus and Works separately, even if they have purposes of Tourism promotion, the influence of the peace treatment on the change of the countrie’s image was defined, the effectiveness of every campaign was specified and which were the ones that had the greatest impact and the impacts of the strategies implemented in tourism promotion were stablished.